Agri-environmental aspects of the activity of farms with different production profiles - Harasim, Adam; Madej, Andrzej; Zarychta, Mariusz (Polish Journal of Agronomy, 2021)
The results of own research and literature data indi- cate that the specialization (different production profiles) of farms may contribute to specific threats to the natural environ- ment. Each type of farm exerts pressure on the environment to a greater or lesser extent, which was confirmed by agri-envi- ronmental indicators. Accordingly to literature data the greatest threat to the environment (water pollution) pose pig farms due to the high stocking density that contributes to unfavorable (exces- sive) balances of minerals and soil organic matter. Large posi- tive balances indicate the potential losses of these components, mainly due to their leaching to groundwater and surface waters, and consequently to their pollution (eutrophication). On the other hand, farms with field crops had high risk of decrease in soil fer- tility due to negative balances of nutrients. The smallest threat to the natural environment and soil fertility were observed for farms with a mixed plant-animal production as well as cattle farms specializing in milk production (with optimal livestock density of about 1 DJP ha-1). Under certain conditions, cattle farms may have too high balances of soil organic matter, and at the same time negative balances of NPK minerals.